The psychology of persecutory ideation I: a questionnaire survey. - Freeman, D; Dunn, G; Garety, P; Bebbington, P; Slater, M; Kuipers, E; Fowler, D; Green, C; Jordan, J; Ray, K (2005)
Paranoia is a complex phenomenon that is likely to arise from a number of factors. In a recent cognitive model of persecutory delusions, three key factors are highlighted: anomalous experiences, emotion, and reasoning. In the first of two linked studies, we report a questionnaire survey of nonclinical paranoia designed to assess the theoretical model. A nonclinical population (N = 327) completed measures of paranoia, anomalous experiences (hallucinatory predisposition, perceptual anomalies), emotion (depression, anxiety, self-focus, stress, interpersonal sensitivity), and reasoning (need for closure). Paranoia was best explained by separation anxiety, depression, fragile inner self, hallucinatory experiences, discomfort with ambiguity, stress, self-focus, perceptual anomalies, and anxiety. The findings are consistent with the central predictions within the model of paranoia.